2015
DOI: 10.3389/fimmu.2015.00340
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Chronic Kidney Disease with Diabetes Mellitus and Cardiovascular Diseases as Its Comorbidities

Abstract: Chronic kidney disease (CKD), diabetes mellitus (DM), and cardiovascular diseases (CVD) are complex disorders of partly unknown genesis and mostly known progression factors. CVD and DM are the risk factors of CKD and are strongly intertwined since DM can lead to both CKD and/or CVD, and CVD can lead to kidney disease. In recent years, our knowledge of CKD, DM, and CVD has been expanded and several important experimental, clinical, and epidemiological associations have been reported. The tight cellular and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 191 publications
1
51
1
1
Order By: Relevance
“…[811] The mechanisms by which elevated dietary NaCl promotes disease apart from elevated blood pressure are diverse, and appear to include endothelial cell damage, alterations in the sympathetic nervous system which regulates the cardiovascular and renal systems, and enhanced inflammatory responses. [7,10,12,13] High NaCl promotes inflammatory responses in vitro and in vivo by inhibiting anti-inflammatory regulatory T cells (Treg), promoting pro-inflammatory Th17 T cells, and enhancing production of inflammatory cytokines. [8,1416] In addition, to help form fibrotic lesions, monocytes can differentiate into fibroblast-like cells called fibrocytes, and we observed that high concentrations of NaCl in tissue culture potentiate human fibrocyte differentiation, and reduce the ability of the endogenous fibrocyte differentiation inhibitor Serum Amyloid P to inhibit fibrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…[811] The mechanisms by which elevated dietary NaCl promotes disease apart from elevated blood pressure are diverse, and appear to include endothelial cell damage, alterations in the sympathetic nervous system which regulates the cardiovascular and renal systems, and enhanced inflammatory responses. [7,10,12,13] High NaCl promotes inflammatory responses in vitro and in vivo by inhibiting anti-inflammatory regulatory T cells (Treg), promoting pro-inflammatory Th17 T cells, and enhancing production of inflammatory cytokines. [8,1416] In addition, to help form fibrotic lesions, monocytes can differentiate into fibroblast-like cells called fibrocytes, and we observed that high concentrations of NaCl in tissue culture potentiate human fibrocyte differentiation, and reduce the ability of the endogenous fibrocyte differentiation inhibitor Serum Amyloid P to inhibit fibrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation has a vital role in the development of DN. High levels of blood glucose and hemodynamic disorder may cause apoptosis and shedding of kidney cells, including podocytes and proximal tubular epithelial cells, leading to the activation of leukocyte, along with the increasing recruitment of inflammatory chemokine factors (22).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the kidney, glycosides maintain the cellular transport of sodium and potassium in a variety of tissues, because many drugs are infused into one renal artery, resulting from inhibition of renal tubular function manifested by a profound natriuresis, chlorosis, and diuresis. Coumarins and saponins possess a fantastic anti-inflammatory with antioxidant properties, which plays a protective role during acute kidney injury 23,24 . The flavonoids reversed the increased expression of enzyme modulators and improved kidney function; while alkaloids protect rat's kidney cells against gentamicin-induced glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%